Edukasi Budidaya Akuaponik: Penyuluhan Partisipatif Berbasis Kemitraan Internasional - Tri Yusufi Mardiana; Juita Lusiana Sihombing; Dzulfiqar Ammar Syam; Nur Fadhilah Adimahsyaf; Dwi Aryo Fajar; Ade Irma Nahdliyyah; Benny Diah Madusari; Linayati Linayati; M Bahrus Syakirin; Hazen Mellai Xyza B. Sarian (CV. SINAR HOWUHOWU, 2024)
The high population and development developments have an impact on decreasing the availability of land and waters for the fisheries and agricultural sectors. Another obstacle that people in coastal areas will encounter is the existence of land that is intruded by sea water, so that the process of cultivating fish and plants in one container is hampered. On the other hand, demand for food is increasing. This phenomenon encourages the emergence of cultivation innovations on limited land. Increasingly, efforts are being made to utilize limited land, such as the yard of the house, so that the family's food needs are met. Aquaponic cultivation is an effort to produce food that saves land use and increases the efficiency of nutrient utilization from food waste and fish metabolism. Extension activities and training on aquaponic systems need to be carried out among the community, including workers, households and students, so that people are able to meet their food needs, both from animals and vegetables. This program also aims to provide education about the importance of the benefits of eating fish and vegetables from an early age, especially among children. It is also hoped that this outreach and training program can open up business opportunities for the community. The result of this service activity is that students understand and are interested in carrying out aquaponic system cultivation activities.